2009
DOI: 10.1097/mpg.0b013e31817a24cf
|View full text |Cite
|
Sign up to set email alerts
|

Is Endoscopic Retrograde Cholangiopancreatography Valuable and Safe in Children of All Ages?

Abstract: ERCP is a safe and valuable procedure for children of all ages with suspicion of pancreaticobiliary diseases. Indications for ERCP are different for children and adults. A laparotomy could be prevented in 12% of children with suspicion of biliary atresia. Further research is required to determine the role of MRCP versus ERCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 17 publications
3
42
0
2
Order By: Relevance
“…Strikingly, in our study, both the overall complication rate of 4.76% and the post-ERCP pancreatitis rate of 3% were lower than or similar to the respective adult rates of 6% to 10% and 3% reported in a systematic review [28] and lower than the rates of 8% and 4% reported by a prospective multicenter study [28,29]. No complications were seen in infants younger than 1 year, supporting a previous series demonstrating the safety of ERCP for infants [24].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Strikingly, in our study, both the overall complication rate of 4.76% and the post-ERCP pancreatitis rate of 3% were lower than or similar to the respective adult rates of 6% to 10% and 3% reported in a systematic review [28] and lower than the rates of 8% and 4% reported by a prospective multicenter study [28,29]. No complications were seen in infants younger than 1 year, supporting a previous series demonstrating the safety of ERCP for infants [24].…”
Section: Discussionsupporting
confidence: 53%
“…The reported incidence of ERCP-related morbidity in children ranges from 0% to 28.5%, with pancreatitis being the most common complication [3,13,17,[24][25][26][27]. Strikingly, in our study, both the overall complication rate of 4.76% and the post-ERCP pancreatitis rate of 3% were lower than or similar to the respective adult rates of 6% to 10% and 3% reported in a systematic review [28] and lower than the rates of 8% and 4% reported by a prospective multicenter study [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) is an ideal method for obtaining an accurate anatomic structure of the biliary tree and pancreatic ducts, but it is invasive and may involve the risk of acute cholangitis, pancreatitis, or bile leakage. Therefore, its use has been restricted in the diagnosis of children because of the instruments and the technology [8].…”
Section: Discussionmentioning
confidence: 99%
“…ERCP has 95%-100% success rate and 3.2%-7.7% complication rate (4,5,(14)(15)(16)(17). Effect of sphincterotomy on the papilla such as biliopancreatic reflux, cholangitis, and the risk of papillary stenosis is unclear in children over the long-term.…”
Section: Discussionmentioning
confidence: 99%